Assessment of relationship between Macro Ergonomic conditions and employees work satisfaction Touse-eh and Omran factory - M. Rismanchian; S. Porabdian; N. Amini; E. Habibi (Salāmat-i kār-i Īrān, 2008)
Background and aims   Background and aim: Macro ergonomics is a social - technical attitude which in the manner of top down proceeds to look at organization planning , work- system and also planning of human - machine , human -environmental , human- job interaction and emphasizes on employees participation and make plenty use of it.   Methods   This descriptive - analytical study is of cross - sectional type. Data gathering method  is based on observation and questionnaire. The society under study includes 83 personnel (employees) of a factory which is a subsidiary of Iran Khodro. We used two questionnaires in this  study. One is questionnaire to verify macro ergonomic situation which planned and consisted of  30 questions that investigated different factors in working environment and was verified in terms  of stability and reliability (cronbach alpha = 0.72) and the other one was Minnesota job satisfaction  questionnaire which was distributed among people.   Results   This research shows over 1,500 extended hour's male workers, 69 percent of whom  reported "Chronic or Frequent" back pain, while 52 percent reported "Chronic or Frequent" wrist  pain. Sleep deprivation could possibly be damaging in terms of muscle, ligament, or tendon  injury. With the average extended-hours employee sleeping only 5.1 hours to 5.5 hours each day when working a night shift, they could face an increased risk of ergonomic injuries. The mean age of people under investigation is 30.8. Most people are in age group of 26-30 (44.6%) most  individuals have 4 to 7 years working experience (56.6%). Macro ergonomic mean score in total  society under study was obtained as 59.8. The highest score of job satisfaction has been related to middle managers (69.2). Pearson correlation test showed that there was a direct relationship between general domain of macro ergonomic and job satisfaction.   Conclusion   There is a consistency between main enhanced results in our study in terms of macro ergonomic situation with the result of similar studies of barariyan (2006) and rajabzadeh (2002) that have used RSI (Relative Stress Index). Also there is a correlation between the result of  our study job satisfaction with the results of similar studies such as Bassy's (2002) in Swedish employees , Garcia and Molina's (1999) in Spanish employees and the result of Partovi study  (2006) in Esfahan steel plant employees and Davari's (2003) in employees of Esfahan Shahid PowerStation.